Hosting the Commonwealth Games : will it boost India’s soft power? - Ajaya Kumar Das (2011)
India’s decision to host the Commonwealth Games seems to have become less popular in the country for its reported oganisational failures in the run-up to the Games. Staging the Games will not help much to advance its